Proceedings-Of-The-13th-Annual-Conference-In-Accounting - Studies On Accounting For Changes In General And Specific Prices - Empirical-Research And Public-Policy Issues - Preface - Dopuch, Nicholas (Journal of Accounting Research, 1978)
Preface